2011
DOI: 10.1159/000319536
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Replication of 50 Reported Asthma Risk Genes Identifies a SNP in RAD50 as Associated with Childhood Atopic Asthma

Abstract: Objectives: Asthma is a childhood disease that is strongly influenced by genetic factors. We sought to replicate an association between single nucleotide polymorphisms (SNPs) of the top-ranked candidate genes and childhood atopic asthma in Perinatal Risk of Asthma in Infants of Asthmatic Mothers (PRAM) study subjects. Methods: Using data from a systematic literature search and an exploratory genome-wide association study conducted in a subset of the PRAM cohort, we followed a strict procedure to generate a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
(30 reference statements)
1
28
1
2
Order By: Relevance
“…Although three SNPs, rs1801275 (−1902G/A), rs1805012 (1291T/C) and rs1805010 (−223G/A) demonstrated associations with asthma in previous studies (1113), only rs1805012 exhibited an association with asthma (dominant model; P=0.03) in the current study. To further investigate the effect of IL-4R SNPs in asthma, eight tag SNPs of the IL-4R region were investigated for an association with asthma, to the best of our knowledge, for the first time.…”
Section: Discussioncontrasting
confidence: 76%
“…Although three SNPs, rs1801275 (−1902G/A), rs1805012 (1291T/C) and rs1805010 (−223G/A) demonstrated associations with asthma in previous studies (1113), only rs1805012 exhibited an association with asthma (dominant model; P=0.03) in the current study. To further investigate the effect of IL-4R SNPs in asthma, eight tag SNPs of the IL-4R region were investigated for an association with asthma, to the best of our knowledge, for the first time.…”
Section: Discussioncontrasting
confidence: 76%
“…[2526] The IL-4Rα gene is highly polymorphic and several SNPs have been associated with different immune-related disorders, including atopy and asthma, although not without discrepancies. [810272829] The rs1805010 polymorphism (A→G) is a type of ‘gain-of-function’ mutation, which results in substitution of isoleucine for valine (I75V) in the extracellular domain of IL-4Rα subunit; in vitro , this mutant receptor with enhanced IL-4 signaling appears to promote a sustained phosphorylation and hence, keep STAT6 transcription factor abnormally active, even upon withdrawal of IL-4 stimulation. [2830] The rs1801275 (A→G) is another gain-of-function mutation also aberrantly enhancing signal transduction, which results in glutamine being substituted by arginine (Q576R) in the intracellular domain of IL-4Rα; it is situated beside the critically important tyrosine-2 residue, which is part of the docking site for STAT6.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma runs in families and is clearly heritable, but patterns of inheritance are complex and genetic studies have shown poor replication, and loci which have been replicated generally explain a very small proportion of the heritability, with small effect sizes [5,6]. The rapid increase in the prevalence of asthma seen in the later part of the last century strongly indicates that environmental exposures are highly relevant in the aetiology of wheezing illnesses.…”
Section: Introductionmentioning
confidence: 99%